ANALISIS FAKTOR KINERJA ORGANISASI BADAN KESATUAN BANGSA DAN POLITIK KOTA SEMARANG - Aninda Puri; Hafidha Putri S; Adita Nurshabrina; Susi Hardjati (Universitas Halu Oleo, 2021)
This study aims to analyze performance and determine organizational performance factors in the National and Political Unity Body of Semarang City. This research uses descriptive qualitative research methods. Qualitative data were obtained through various kinds of data collection techniques, including through interviews, document analysis, literature study and selection of informants using purposive techniques, the quality of the data was tested using the Triangulation Technique. In this study, innovation as a process of organizational learning and knowledge creation related to organizational capacity to respond to environmental changes. This research is based on the application of Organizational Ecology Theory and The Punctuation Model and Theory of Strategic Adaptation and Sustainable Change. Based on this theory, organizational innovation can be generated by technological innovation and increased organizational learning capacity and transformation. The results of the study explained that the organizational performance of the National Unity and Political Body of the City of Semarang was not optimal, so there was still much that needed to be improved so that the public's assessment of the level of performance of the office organization would increase.